2014
DOI: 10.1371/journal.pone.0105076
|View full text |Cite
|
Sign up to set email alerts
|

Galleria mellonella Model Identifies Highly Virulent Strains among All Major Molecular Types of Cryptococcus gattii

Abstract: Cryptococcosis is mainly caused by Cryptococcus neoformans. However, the number of cases due to C. gattii is increasing, affecting mainly immunocompetent hosts. C. gattii is divided into four major molecular types, VGI to VGIV, which differ in their host range, epidemiology, antifungal susceptibility and geographic distribution. Besides studies on the Vancouver Island outbreak strains, which showed that the subtype VGIIa is highly virulent compared to the subtype VGIIb, little is known about the virulence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 51 publications
5
60
1
Order By: Relevance
“…An in vivo study using the wax moth model organism Galleria mellonella conversely found that, although not statistically significant, C . bacillisporus/ VGII strains had larger capsules than the other species/genotypes in the C. gattii complex did (43). This may be because during the progression of systematic cryptococcosis, the infecting organism must adapt to various conditions at different time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo study using the wax moth model organism Galleria mellonella conversely found that, although not statistically significant, C . bacillisporus/ VGII strains had larger capsules than the other species/genotypes in the C. gattii complex did (43). This may be because during the progression of systematic cryptococcosis, the infecting organism must adapt to various conditions at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have noted the presence of these cells in C. gattii , although a recent study of infection in G. mellonella larvae observed cells with diameters ranging from 15 to 75 μm (43). Here we report the presence of giant cells in strains of C. deuterogattii /VGII, C. bacillisporus /VGIII, and C. tetragattii /VGIV (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For C. gattii it was demonstrated that major molecular types exhibit a range of virulence potential, with some strains having the potential to be more virulent than others. Differences could be directly correlated to melanin synthesis and the cell and capsule size (Firacative et al 2014). …”
Section: Virulence Traits Of Cryptococcus Neoformans and Cryptococcusmentioning
confidence: 99%
“…mellonella has subsequently been used to study other fungal pathogens including Aspergillus fumigatus,5,7 Histoplasma capsulatum, 8 Paracoccidioides lutzii, Fusarium species 9,10 and other Cryptococcus species 11 (Full list of fungal species tested in G. mellonella is summarised in Table 1). …”
Section: Introductionmentioning
confidence: 99%